Murine model of Bacillus cereus gastrointestinal infection - Rolny, Ivanna Sabrina (2014)
Bacillus cereus is a spore-forming micro-organism responsible for foodborne illness. In this study, we focus on the host response following intragastric challenge with a pathogenic B. cereus strain (B10502) isolated from a foodborne outbreak. C57BL/6J female mice were infected by gavage with strain B10502. Controls were administered with PBS. Infection leads to significant modification in relevant immune cells in the spleen, Peyer's patches (PP) and mesenteric lymph nodes (MLN). These findings correlated with an increase in the size of PP as compared with uninfected controls. Histological studies showed that B. cereus infection increased the ratio of intestinal goblet cells and induces mononuclear cell infiltrates in spleen at 5 days post-infection. Evaluation of cytokine mRNA expression demonstrated a significant increase in IFN-γ in MLN after 2 days of infection. The present work demonstrates that infection of mice with vegetative B. cereus is self-limited. Our findings determined relevant cell populations that were involved in the control of the pathogen through modification of the ratio and/or activation.